2008
DOI: 10.1093/aje/kwn121
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Esophageal Cancer and High-Grade Dysplasia in Barrett's Esophagus: A Systematic Review and Meta-Analysis

Abstract: Barrett's esophagus is a well-recognized precursor of esophageal adenocarcinoma. Surveillance of Barrett's esophagus patients is recommended to detect high-grade dysplasia (HGD) or early cancer. Because of wide variation in the published cancer incidence in Barrett's esophagus, the authors undertook a systematic review and meta-analysis of cancer and HGD incidence in Barrett's esophagus. Ovid Medline (Ovid Technologies, Inc., New York, New York) and EMBASE (Elsevier, Amsterdam, the Netherlands) databases were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
273
8
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 365 publications
(299 citation statements)
references
References 111 publications
13
273
8
5
Order By: Relevance
“…A geographic variation in BE cancer risk has been suggested by another group [46]. Very small differences in the EAC incidence were reported between different geographic regions, with only a slightly higher EAC incidence in the USA and UK compared to other European countries, which is in line with other studies [63,64]. The incidence in Australia and New Zealand was slightly lower than that in the USA and Europe including the UK [63].…”
Section: Risk Factors For Eac or Dysplasiasupporting
confidence: 83%
See 1 more Smart Citation
“…A geographic variation in BE cancer risk has been suggested by another group [46]. Very small differences in the EAC incidence were reported between different geographic regions, with only a slightly higher EAC incidence in the USA and UK compared to other European countries, which is in line with other studies [63,64]. The incidence in Australia and New Zealand was slightly lower than that in the USA and Europe including the UK [63].…”
Section: Risk Factors For Eac or Dysplasiasupporting
confidence: 83%
“…Several systematic reviews and metaanalyses on the EAC risk in BE patients [60,[62][63][64][65][66] are summarized in Table 1. Among these studies, the rate of progression in BE without dysplasia at baseline to EAC is low, ranging from 0.33 % (95 % CI 0.28-0.38 %) to 0.598 % (95 % CI 0.505-0.691 %) annually [65,66].…”
Section: Risk Factors For Eac or Dysplasiamentioning
confidence: 99%
“…Several individual studies (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)27) and 2 systematic reviews (that produced essentially identical results despite slightly different methodologies (16,17)) have reported that statin use, and particularly statin use combined with a cyclo-oxygenase inhibitor, is associated with a reduced incidence of esophageal adenocarcinoma. This has been reported in cohort studies and case-control studies of Barrett's patients and population-based studies compared to population-based controls, although not all studies are in agreement (28).…”
Section: Discussionmentioning
confidence: 99%
“…(3,4). It is accepted that metaplastic transformation of the esophageal squamous mucosa to intestinaltype mucosa (Barrett's esophagus (BE)) is a premalignant phenotype, although the overall rate of progression is relatively low (probably about 1 in 300 patients per year, or less) (5)(6)(7) and this has allowed the development of surveillance and localised treatment strategies such as radio-frequency ablation as means of preventing the development of EAC (8). However overall mortality from EAC remains considerable with 5-year survival less than 25% (9).…”
Section: Introductionmentioning
confidence: 99%
“…Esophageal cancer occurs more frequently in men than women 21 and men progress to invasive carcinoma from Barrett's esophagus at twice the rate of their female counterparts 22 . While ER had been demonstrated in esophageal mucosa in 1983 23 , a second isoform of the receptor was described in 1996 24 and this warranted further characterisation and classification its presence in esophageal tissue.…”
Section: Estrogen and Esophageal Cancermentioning
confidence: 99%